Does the age difference between the doctor and the patient matter - communication between the doctor and the young patient - Wróblewski, Hubert; Zimna, Aleksandra (Journal of Education, Health and Sport, 2021)
Introduction and purpose of work: The contact between doctor and patient is an element that builds mutual trust, which translates into the quality and effectiveness of treatment. This is especially important for adolescent patients, who expect attention and understanding of their problems. In addition, they start visiting the doctor themselves, so it is very important that they do not become discouraged by the lack of understanding of the doctors and that they do not avoid visits in the future. Currently, the average age of a doctor in Poland is over 50 years. The aim of the study is to investigate the influence of a doctor’s age on his contact with a teenage patient. Material and method: The results of the study were obtained on the basis of the questionnaire survey. Results: 54 respondents aged 16-19 participated in the study. The vast majority (64.8%) consider a person under 30 years of age to be a young doctor, 29.6% under 40 years of age. Almost 67% declare that it is more likely to visit a young doctor. 87% of respondents find it easier to establish contact with a younger medic. For 68.5% of respondents, a visit to a senior doctor is more embarrassing. 88.9% of teenagers find it easier to admit embarrassing matters to younger medics. 66.7% declare that for them being more practiced is more important than easier contact with doctor. Two out of three teenagers are more stressed about visiting older doctor. Conclusions: Teen patients definitely prefer visits to younger doctors. Despite the greater stress and resistance to visiting older, more experienced doctors, young patients choose them. Training for senior physicians on contact with young people should be considered to reduce the proportion of people avoiding medical appointments due to difficulties in making contact in the future.